An Investigation Into the Effects of Destination Sensory Experiences at Visitors’ Digital Engagement: Empirical Evidence From Sanya, China - Ai, Jin; Yan, Ling; Hu, Yubei; Liu, Yue (Frontiers in Psychology, 2022)
This study investigates the mechanism of how sensory experiences influence visitors’ digital engagement with a destination through establishing a strong bond and identification between a destination and tourist utilizing a two-step process. First, visitors’ sensory experiences in a destination are identified through a content analysis of online review comments posted by visitors. Afterwards, the effects of those sensory experiences on visitors’ digital engagement through destination dependence and identification with that destination are examined. Findings suggest that sensory experiences are critical antecedents of visitors’ bond and identification with a destination. Visitors’ positive destination-related sensory experiences increase their dependence on and identification with the destination, and this dependence and identification positively influence their digital engagement behavior on social media.